2014
DOI: 10.1371/journal.pone.0086261
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Seroprevalence of Rabies Virus Neutralizing Antibodies and Associated Factors in a Colorado Population of Big Brown Bats (Eptesicus fuscus)

Abstract: In 2001–2005 we sampled permanently marked big brown bats (Eptesicus fuscus) at summer roosts in buildings at Fort Collins, Colorado, for rabies virus neutralizing antibodies (RVNA). Seroprevalence was higher in adult females (17.9%, n = 2,332) than males (9.4%, n = 128; P = 0.007) or volant juveniles (10.2%, n = 738; P<0.0001). Seroprevalence was lowest in a drought year with local insecticide use and highest in the year with normal conditions, suggesting that environmental stress may suppress RVNA production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
4
8
0
Order By: Relevance
“…This supports previous observations that bats could harbor exposure events without any impact on their mortality rate. These results are indeed comparable to the survival analysis computed for big brown bats ( Eptesicus fuscus ) affected by RABV in the United States [ 77 ] and for a Myotis myotis colony affected by EBLV-1 in Spain [ 73 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This supports previous observations that bats could harbor exposure events without any impact on their mortality rate. These results are indeed comparable to the survival analysis computed for big brown bats ( Eptesicus fuscus ) affected by RABV in the United States [ 77 ] and for a Myotis myotis colony affected by EBLV-1 in Spain [ 73 ].…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study, female serotine bats were shown to be more exposed to EBLV-1 than males, probably due to their gregarious social behavior, males being more solitary [ 88 ]. Similar findings were also highlighted in the framework of RABV transmission in Brazilian free-tailed bats [ 89 ] big brown bats [ 77 ] and in vampire bats [ 90 ]. In our study, occurring in breeding colonies, only females were assessed and we have shown evidence from site B that seroreversions were significantly more frequent than seroconversions.…”
Section: Discussionsupporting
confidence: 76%
“…Given that the spread of rabies outbreaks may be favored by the interchange of bats between colonies [ 59 ], populations with infected individuals that are easily accessible may promote outbreaks of the disease more efficiently and over a shorter time scale. It is also important to note that, as found in previous studies, infection rates in a population may be related to specific characteristics, such as genetic diversity, the physiological condition of individuals [ 60 , 61 ], and immunity levels [ 6 , 62 ]. In this case, some D .…”
Section: Discussionmentioning
confidence: 99%
“…"Natural" boosting of virus-specific IgG antibody levels in ERBs that had been previously infected with Marburg virus was observed during a recent experimental transmission study shortly after documenting virus infection and seroconversion in naïve contact bats 36 . Others have reported periodic boosting of rabies virus neutralizing antibody titers in a wild colony of big brown bats (Eptesicus fuscus) 47 . Second, we used a goat anti-bat IgG conjugated to horseradish peroxidase as the secondary antibody in our system.…”
Section: Filovirus Antigen Lysate Cutoffmentioning
confidence: 99%